THE EFFECT OF ROA, ROE, AND EPS ON SHARE PRICE IN THE RETAIL SUBSECTOR 2019 – 2022 - Wahyuningtiasari, Defi; Agusti, Orriyana; Madhista, Shielda Adeliani; Ardianti, Yessi Nurviana; Nugroho, Muhammad Awal Satrio; Navira, Cherry Austin (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) on stock prices. This research was conducted on retail industry companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling technique used random sampling method and obtained 9 companies as research samples. Methods of data analysis using multiple regression analysis. The results of this study indicate that ROA and ROE partially have no significant effect on stock prices, but EPS partially has a significant effect on stock prices. However, ROA, ROE, and EPS simultaneously influence stock prices.